2019
DOI: 10.3758/s13428-019-01205-5
|View full text |Cite
|
Sign up to set email alerts
|

Do current statistical learning tasks capture stable individual differences in children? An investigation of task reliability across modality

Abstract: Do commonly used statistical-learning tasks capture stable individual differences in children? Infants, children, and adults are capable of using statistical learning (SL) to extract information about their environment. Although most studies have looked at group-level performance, a growing literature examines individual differences in SL and their relation to language-learning outcomes: Individuals who are better at SL are expected to show better linguistic abilities. Accordingly, studies have shown positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
111
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 49 publications
6
111
1
Order By: Relevance
“…Another potential explanation for our null result on the association between serial reaction time performance and grammatical proficiency may concern the reliability of the disruption peak as an individual measure of statistical learning in the serial reaction task (see Arnon, 2019;West et al, 2017 for discussions of the low psychometric properties of the currently available measures to assess individual differences in statistical learning). Our disruption peak measure had a split-half reliability of 0.62, with a 95% confidence interval ranging from 0.38 to 0.76.…”
Section: Discussion Experimental Studymentioning
confidence: 96%
“…Another potential explanation for our null result on the association between serial reaction time performance and grammatical proficiency may concern the reliability of the disruption peak as an individual measure of statistical learning in the serial reaction task (see Arnon, 2019;West et al, 2017 for discussions of the low psychometric properties of the currently available measures to assess individual differences in statistical learning). Our disruption peak measure had a split-half reliability of 0.62, with a 95% confidence interval ranging from 0.38 to 0.76.…”
Section: Discussion Experimental Studymentioning
confidence: 96%
“…Further, we showed that an individual's stronger change from a positive ERP effect on day one to a negative ERP effect on day two was correlated with stronger positive behavioral changes (i.e., more correct answers on day two compared to day one). These results have to be interpreted with caution because individual differences in statistical learning show questionable reliability (Arnon, 2019;Siegelman et al, 2017aSiegelman et al, , 2017bWest et al, 2018) and the behavioral performance was not above chance at the group level. However, our results at the individual level are in line with our results at the group level.…”
Section: Discussionmentioning
confidence: 91%
“…Since these measures were acquired in the same task, their correlation should not be over-interpreted. Recently, several concerns have been raised about the reliability of offline measures of individual differences in statistical learning (Siegelman et al, 2017a(Siegelman et al, , 2017bWest et al, 2018;Arnon, 2019). In the present study, we address some of these concerns, as…”
Section: Limitationsmentioning
confidence: 88%
See 2 more Smart Citations